Protection Against Violence - Sztranyiczki, Szilárd (Children’s Rights in Regional Human Rights Systems, 2024)
Violence against children includes all forms of physical or mental violence, injury or abuse, neglect or negligent treatment, maltreatment, and exploitation, including sexual abuse.Under international law, States have an obligation to protect children from various forms of violence. The United Nations Convention on the Rights of the Child is the primary international human rights instrument addressing children’s protection against violence. The Convention came into force in September 1990 and has been ratified by 195 countries, making it ‘the single most ratified treaty in existence’. However, only two countries, the United States and Somalia, have not yet ratified the Convention.This chapter analyses the specific types of violence against children and the response of the major regional human rights systems: the African, the Inter-American and the European [human rights system], the Inter-American and the African human rights systems.Keywords: physical violence, mental violence, injury, abuse, neglect, negligent treatment, maltreatment, exploitation, Convention on the Rights of the Child, regional human rights systems